Pengendalian Perilaku Tidak Aman dengan Behaviour Based Safety dan 5W1H pada Industri Manufaktur - Rizqullah, Rifqi; Ikhwana, Andri; Sa’duddin Taptajani, Dedi (Jurnal Kalibrasi, 2025)
Workplace accidents still frequently occur in the industrial world, especially in the manufacturing industry, particularly on manufacturing production lines. Based on observations, most accidents are caused by unsafe behavior on the part of workers, such as rushing, carelessness, and non-compliance with work procedures. This study aims to identify and analyze the causes of unsafe behavior and provide solutions through a Behavior Based Safety (BBS) approach combined with the 5W1H method. Data was collected through direct observation, interviews, and documentation of workplace accidents. The analysis was conducted using the ABC (Antecedents–Behavior–Consequences) tool, which maps the triggers of behavior (antecedents), the behavior displayed (behavior), and the consequences (consequences). The results of the study show that the application of BBS is effective in increasing workers' awareness of work safety. Routine observations and direct feedback have been proven to reduce the risk of workplace accidents. The findings from the ABC analysis can be used as a basis for formulating more targeted strategies for improvement and accident prevention.